Implikasi Penerapan Activity Based Costing System Terhadap Kinerja Perusahaan Dan Keunggulan Bersaing - Diah Anugrah Sharasanti (BIP's JURNAL BISNIS PERSPEKTIF, 2020)
The strategy for determining the accurate production cost is one way for the company to compete among its competitors. Activity Based Costing assumes allcosts have a cause, and the causes can be managed so that the costs charged can be effective and efficient. Several studies have shown that there are differences in production costs between calculations using traditional methods and Activity Based Costing. Previous studies have shown that production costs are more accurate when using the Activity Based Costing method of calculation. Bjornenak and Mitchell (1999) in Rendy and Devie (2013) argue that Activity Based Costing is a system that is promoted and adopted as a basis for strategic decision-making and to improve earnings performance. According to Reimann (1990) the use of the Activity Based Costing system encourages companies to produce products that have competitive advantages. The results of several studies show that the ability of the Activity Based Costing system can not only measure product costs accurately, but the information generated can be used for various other strategic interests within the company, and the implementation of the Activity Based Costing system is not only focused on the financial aspects, but also on other nonfinancial aspects which are indicators of the success of company performance.